Comparison of Antibacterial Effect of Four Irrigation Solutions in Primary Root Canal Infections: A Clinical Study - Khedmat, Sedigheh; Fakhari, Nooshin; Emaneini, Mohammad; Beigverdia, Reza (Iranian Endodontic Journal, 2018)
Introduction: Reducing the bacterial count from the root canal system is one of the main stages in root canal treatment. The aim of the present clinical study was to compare the antibacterial effect of four intracanal irrigants in primary endodontic infections using both microbiological culture and quantitative Real-time Polymerase Chain Reaction (qRT-PCR) technique. Methods and Materials: Forty patients with primarily infected single rooted premolars were selected and then randomly divided into 4 groups according to the intra canal irrigant used: 5.25% Sodium hypochlorite (NaOCl), Hypoclean (Ogna Laboratori Farmaceutici, Muggiò, Italy), 2% chlorhexidine glouconate (CHX) and CHX-Plus (Vista Dental Products, Racine, WI, USA). Samples were collected before and after chemomechanical preparation and were evaluated by bacterial culture and RT-PCR technique for Enterococcus faecalis and Fusobacterium nucleatum. Data analyzed by repeated measured ANOVA. The significance level was set at 0.05. Results: Four irrigation solutions significantly reduced the total numbers of cultivable bacteria (P<0.05). No statistically differences were found among the antibacterial effects of 5.25% NaOCl (99.93%), Hypoclean (99.94%), 2% CHX (99.77%) and CHX-Plus (99.83%) in reducing cultivable bacteria. Enterococcus faecalis and Fusobacterium nucleatum were no longer detected after preparation using four irrigants (100% reduction). Conclusions: All tested irrigants including 5.25% NaOCl, Hypoclean, 2% CHX and CHX-Plus significantly reduced the number of bacterial colonies in primary endodontic infections. Keywords: CHX-Plus; Endodontic Infection; Enterococcus faecalis; Fusobacterium nucleatum; Hypoclean